Impact of Liquidity, Ownership, Global Financial Crisis, and Capital Adequacy Ratio on Indonesian Banking Profitability Period 2007-2016 - Winoto, Agustinus; Bustaman, Yosman (Journal the Winners: Economics, Business, Management, and Information System Journal, 2020)
The purpose of the research was to analyse the effect of liquidity, ownership, and global financial crisis on Indonesian Banking profitability. The research focused on conventional bank exclude sharia-bank and rural bank/BPR, owned by foreign-party, local-party or mixed-party, period 2007 to 2016. Data were retrieved from Indonesia Bank regulator which is Otoritas Jasa Keuanganâ€™s website. For liquidity, liquidity ratio, loan to funding ratio, and cash ratio were used. Meanwhile ownership and global financial crisis used dummy variable. The research divided bank to foreign and mixed party, and local bank in the years of crisis that were 2008 and 2009. Ordinary Least Square method were used with Net Interest Margin as dependent variable, a control variable, and capital adequacy ratio. The result finds that there is no significant connection between liquidity and ownership on profitability, while crisis has significant connection on profitability.Â